Islamic Educational Values in Javanese Wedding Traditions on the Slopes of Mount Bromo - Ahmad Zubaidi; Dyah Nawangsari; Mashudi; Ubaidillah (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
The integration of Javanese wedding customs into Islamic religious education is an intriguing topic to investigate, particularly within multicultural communities on the slopes of Mount Bromo. This study aims to describe how Islamic educational values are integrated into Javanese wedding practices and to explain the mechanisms through which Islamic meanings are reinterpreted in each stage of the ceremony. The study contributes to discussions on cultural and religious acculturation in the context of values education. Employing a descriptive qualitative approach with an ethnographic method, data were collected through in-depth interviews, participant observation, and documentation to understand the symbols, meanings, and practices embedded in wedding rituals. The data were analyzed using an interactive analysis technique (data reduction, data display, and conclusion drawing/verification), complemented by thematic coding to identify patterns of meaning and forms of value integration. The findings indicate that traditions such as siraman, seserahan, sungkeman, and sepasar undergo a process of reinterpreting Islamic meanings through mechanisms of demystification, re-theologization, and values education without eliminating the essence of local culture. This integration not only demonstrates harmony between Islamic principles and local wisdom but also functions as a contextual medium for moral, social, and spiritual values education. The study concludes that tradition is not an obstacle to religious practice; rather, it serves as a strategic avenue for transforming Islamic values through living cultural expressions that are accepted by the community.